Spirituality and Social Support as Predictors of Resilience among Elderly Cancer Patients' Informal Caregivers in Punjab, Pakistan - Mussarat Hussain; Dr. Khalil Ahmad (Journal of Management Practices, Humanities and Social Sciences, 2021)
In the context of informal caregiving studies, the use of resilience as a coping mechanism for mitigation of informal care burden is regarded as crucial. More than half of the caregivers of elderly cancer patients experience at least one suspected psychiatric symptom, including depression, anxiety, alcohol abuse/dependence, and post traumatic stress disorder. Besides this, various studies have supported the role of social support and spirituality as predictors of resilience in protecting and maintaining the physical and psychological health of informal caregivers. But, by analyzing previous literature, there is a dearth of empirical research in the Pakistani context which may examine spirituality and social support as predictors of resilience among informal caregivers of elderly cancer patients. To fill this research gap, the current study aimed to analyze spirituality and social support as predictors of resilience among informal caregivers of elderly cancer patients. In this regard, the current study was conducted using a quantitative research design. By using a purposive sampling technique, the data was collected from 200 informal caregivers of elderly cancer patients from the following hospitals: In mol Cancer Hospital, Cancer Care Hospital Lahore, the Oncology ward of Mayo Hospital Lahore, and the Oncology ward of Jinnah Hospital Lahore. An interview schedule was used as a tool of data collection by adopting the following scales: Caregiver’s Resilience Scale, Caregiver’s Spirituality Scale, and MOS Social Support Scale. The study results were analysed using SPSS software, and the descriptive section of the results indicated that the larger proportion of informal caregivers were male, dependent upon their families, aged between 24 and 29, and had only a secondary level of education. Furthermore, when the inferential statistics of the study's correlation and regression analysis tests were used, the results revealed that caregiver spirituality and social support had a significant and positive effect on the caregiver's resilience to care giving burden.